Duolingo application: Its impact on students’ grammar in writing context - Ari Ilsanti; Rosi Anjarwati (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2025)
Grammar is one of the English components that learners consider the most crucial key or foundation for understanding the meaning of a phrase accurately and efficiently. The goal of this study is to determine whether the Duolingo application improves students' grammatical competence in writing recount texts at SMK Negeri 1 Gudo. The study design was a quasi-experiment with two groups: experimental using Duolingo and control without Duolingo. Data was gathered through writing pre-test and post-test about personal recount. ANCOVA was used to ensure differences in results between groups after the treatment. The result reveals that there is a significant different of grammar achievement in writing context between the students who learnt using Duolingo and those who did not.